Partisipasi ktd (karang taruna desa) dalam meningkatkan kesejahteraan sosial di desa tolotio kecamatan bonepantai kabupaten bone bolango - Pratiwi Ntoe; Djamila Podungge; Siske Anani (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This scientific paper aims to determine the participation of youth organizations in improving social welfare in Tolotio Village, Bonepantai Sub-district, Bone Bolango Regency. The report method used is a qualitative method. This scientific paper takes place at the Tolotio Village office, Bonepantai Sub-district, Bone Bolango Regency. The data collection techniques used were observation, interview, identification and documentation. The results of this scientific paper report show that the activeness of the youth organization is still lacking and inadequate facilities greatly affect the activities to be carried out. the involvement of the youth organization is still lacking because they choose to look for work outside the village because the jobs in the village are still lacking so that more youth choose to migrate with the aim of improving their family's standard of living.